Dentists' use of validated child dental anxiety measures in clinical practice: a mixed methods study - Alshammasi, Hussain; Buchanan, Heather; Ashley, Paul (Wiley, 2018)
Background: Assessing anxiety is an important part of the assessment of a child presenting for dental treatment; however, the use of dental anxiety scales in practice is not well-documented.